Formula Optimization and Quality Analysis of High-fiber Acid Slurry Tofu - Chunhua YANG; Wen QI; Likun REN; Yadong SUN; Guang ZHANG; Yang YANG; Na ZHANG (Shipin gongye ke-ji, 2022)
This article aimed to improve the utilization of by-products of tofu and produce high-quality tofu, on the basis of the production process of acid slurry tofu, bean dregs and transglutaminase (TG enzyme) were added to it. The soybean-water ratio, soybean dregs addition, acid slurry addition and transglutaminase addition were chosen as four factors, sensory score was used as evaluation index to optimize the preparation process of high-fiber acid slurry tofu, and the product was compared with the traditional acid slurry tofu, the dietary fiber content, sensory evaluation, texture characteristics, protein structure and microstructure of the two were analyzed. Results showed that, the optimal process results were as follows: Soybean-water ratio 1:4.6, 15% soybean dregs addition, 21% acid slurry addition, 0.3% transglutaminase addition. The order of influence on the sensory score of high-fiber acid slurry tofu was: Soybean dregs addition amount> transglutaminase addition amount> acid slurry addition amount> soybean-water ratio. Under this condition, the dietary fiber content of high-fiber acid slurry tofu increased from 0.26% to 2.15%. The texture characteristics were similar to traditional one, texture was not hardened due to the increasing of dietary fiber, flavor was strong, internal tissue was uniform and flexible. From FTIR spectrum, it could be seen that transglutaminase enhanced the cross-linking between protein and protein, and the protein gel structure was more compact. The microstructure was more dense and orderly.